The meta‐analytical paradigm in an in silico hybrid: Pathways and networks perturbed during exposure to varying degrees of hypobaric hypoxia. Issue 7 (21st March 2017) - Paul, Subhojit; Bhargava, Kalpana; Ahmad, Yasmin
Abstract : Purpose: Computational biology has opened a gateway to omics data analysis and shifted the focus from molecules to systemic molecular networks in the domain of hypobaric hypoxia (HH). Yet there are no meta‐analytical investigations circumventing constraints such as organism (rat/human), HH exposure conditions (acute/chronic), and the tissues that can be investigated simultaneously in the realm of wet lab experiments. Experimental design: We analyzed 154 differentially expressed proteins upon HH exposure using Ingenuity Pathway Analysis (IPA) tool, without the constraint of using a single organism or tissue type, to determine the most significant pathways and networks that are perturbed across a range of HH conditions. Results: We found acute phase response signaling, farsenoid X receptor/retinoid X receptor activation, liver X receptor/retinoid X receptor activation, clathrin‐mediated endocytosis signaling, mitochondrial dysfunction, production of nitric oxide and ROS in macrophages, and integrin signaling to be the most significant universally perturbed pathways. Unique protein–function relationships have also been highlighted. Conclusion and clinical relevance: This meta‐analysis provides a list of specific pathways and networks across two model organisms that are perturbed due to HH exposure irrespective of its duration/intensity. Thus, it will be a map of important pathways and proteins to look at when exploring effects of HH exposure irrespective of tissue/organism chosen, particularly in the context of prophylactic/therapeutic targets.